2016
DOI: 10.18203/2349-2902.isj20162745
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of breast lumps in a given population: an institutional study

Abstract: INTRODUCTIONBreast cancer is the leading malignancies in the world and accounts for 15.4% of all malignancies and appears to be increasing with time. Breast lump is the most common reason for presenting to surgery department.Various types of lesion from inflammation to carcinoma can affect breast. Some lesions are common in young females while others in elderly age group. Early presentation and prompt diagnosis is essential to relieve anxiety of non-neoplastic conditions, and in case of carcinoma, it can save … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The age of studied population ranged from 15 to 60 years with mean age of 33.11 years. Similar findings were reported by Goyal et al 31 who conducted a study in India and found most of the breast cancer patients belong to 15–70 years age.…”
Section: Discussionsupporting
confidence: 89%
“…The age of studied population ranged from 15 to 60 years with mean age of 33.11 years. Similar findings were reported by Goyal et al 31 who conducted a study in India and found most of the breast cancer patients belong to 15–70 years age.…”
Section: Discussionsupporting
confidence: 89%